La pugna de Rusia y China en Asia Central. El caso de Kazajistán - SANTIAGO ORTI, Rafael (Journal of the Spanish Institute for Strategic Studies, 2024)
The current international scenario, with the war in Ukraine in the background, has brought profound and decisive changes to Russia’s backyard. The historical dominance it exercised in Central Asia since Soviet times is gradually being taken over by China through energy and trade agreements in the region, progressively displacing Moscow to a secondary role. The Ukrainian conflict is preventing the Russian Federation from fulfilling its security tasks, one of the few competencies it has maintained in the Central Asian space, which further weakens its position.Kazakhstan is the regional power and main energy producer in the area. Traditionally it has been Russia’s major ally in the region, but it is beginning to distance itself from Moscow, attracted by the substantial investments of Beijing, which is already its main commercial partner and has important energy and economic-commercial interests in the country. However, Russia has significant soft power in the region and will not give up its interests in the country, with which it shares a long border and is its gateway to the rest of the Central Asian republics. Whoever dominates Kazakhstan will dominate Central Asia.